ANALISIS DAYASAING USAHATANI JAGUNG DI KABUPATEN BOLAANG MONGONDOW PROPINSI SULAWESI UTARA - Zulkifli Mantau; Bahtiar .; Aryanto . (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2012)
The Competitiveness Analysis of Maize Farming in Kabupaten Bolaang Mongondow, North Sulawesi Province. The aims of this research are: 1) to analyze the profitability of maize farming in Kabupaten Bolaang Mongondow, 2) to analyze the comparative and competitive advantages of maize farming in Kabupaten Bolaang Mongondow, 3) to analyze the impact of government policy on competitiveness of maize farming in Kabupaten Bolaang Mongondow, 4) to analyze the price changed sensitivity of input, output and wage of labor on comparative and competitive advantages of maize farming. The analysis method uses a Policy Analysis Matrix (PAM). The PAM results showed that private and social profitability of maize farming are Rp. 218 926 and Rp. 3 045 938. Private Cost Ratio of maize farming was 0.97. Domestic Resources Cost Ratio of maize farming was 0.65. The results of Output Transfer and Nominal Protection Coefficient on Output can be indicated that output price in domestic market was lower than output price in international market. The results of Input Transfer and Nominal Coefficient on Input can be indicated that there’s subsidy policy impact in input price of maize farming. In additional, factor transfer result indicated that there’s tax policy impact in domestic factors. The result of Effective Protection Coefficient of maize (0.80) indicates that there’s low protection of maize product in Bolmong. Net Transfer result was negative. The profitability rates of maize farming just only 7 % in private price. Subsidy Ratio to Producers was negative. It means that there’s a high budget of production budget of maize farming in private factor. Finally, based on sensitivity analysis can be shown that the ninth scenario (fertilizer price decreased 10 % and output price increased 30 %) was the best scenario. Informasi tentang dayasaing usahatani jagung di Sulawesi Utara diperlukan sebagai acuan dalam menentukan arah kebijakan dalam pengembangan komoditas jagung. Tujuan dari penelitian ini adalah untuk: 1) Menganalisis aspek profitabilitas usahatani jagung di Kabupaten Bolaang Mongondow, 2) Menganalisis keunggulan komparatif dan kompetitif usahatani jagung di Kabupaten Bolaang Mongondow, 3) Menganalisis dampak kebijakan pemerintah terhadap dayasaing usahatani jagung di Bolaang Mongondow, 4) Menganalisis sensitivitas perubahan harga input, output dan upah tenaga kerja terhadap keunggulan komparatif dan kompetitif usahatani jagung di Bolaang Mongondow. Metode analisis menggunakan Policy Analysis Matrix (PAM). Hasil PAM menunjukkan profitabilitas privat dan sosial usahatani jagung berturut-turut Rp. 218 926 dan Rp. 3 045 938. Private Cost Ratio usahatani jagung sebesar 0.97. Domestic Resources Cost Ratio usahatani jagung sebesar 0.65. Berdasarkan hasil Output Transfer dan Nominal Protection Coefficient on Output menunjukkan harga output di pasar domestik lebih rendah dibanding dengan pasar internasional. Berdasarkan hasil Input Transfer dan Nominal Coefficient on Input menunjukkan bahwa terdapat dampak kebijakan subsidi terhadap harga-harga input pada usahatani jagung. Hasil analisis factor transfer menunjukkan bahwa terdapat dampak kebijakan pajak (retribusi) terhadap faktor-faktor domestik. Hasil Effective Protection Coefficient usahatani (0.80) menunjukkan rendahnya proteksi terhadap produk/ output jagung di Bolmong, sementara hasil Net Transfer menunjukkan hasil yang negatif. Profitability rates usahatani jagung hanya sebesar 7% pada tingkat harga privat, sementara Subsidy Ratio to Producers hasilnya negatif. Hal ini menunjukkan terdapat tingkat anggaran operasional yang besar dalam produksi usahatani jagung, khususnya pada faktor privat. Analisis sensitivitas menunjukkan bahwa skenario ke-9 (harga pupuk turun 10% dan harga output naik 30%) merupakan skenario terbaik.